Current and Future Treatment Options for Hearing Loss - Niknazar, Somayeh; Khoshsirat, Shahrokh (Journal of Otorhinolaryngology and Facial Plastic Surgery, 2018)
Hearing loss is caused by several factors, such as genetic, aging, drug, infection and exposure to loud sound and around 360 million people worldwide have disabling hearing loss. Here, we discuss the current and future strategies for the treatment of hearing loss.